2012
DOI: 10.1007/s12594-012-0149-1
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of magnetite grains — implications for interpreting deformation mechanism

Abstract: In the present study, the grain size (d) and shape of 225 magnetite grains, that crystallized at T>600°C in a syntectonic granite (Godhra Granite, India) are evaluated and implications of data to decipher deformation mechanism of magnetite are discussed. Fractal (ruler) dimension (D) analysis of magnetite grains is performed and it is demonstrated that they show fractal behaviour. Smaller magnetite grains tend to be more serrated than the larger ones, which is manifested in the higher fractal (ruler) dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(28 reference statements)
2
3
0
Order By: Relevance
“…The curves go through a critical region at rates below 10 À10 s À1 in which instabilities develop. The critical value is within the estimated rate of emplacement (10 À9 e10 À10 s À1 ) of a pluton (Vigneresse, 2004;Mamtani, 2012). On the presented diagram (Fig.…”
Section: Instability Developments Caused By the Rheologysupporting
confidence: 75%
See 2 more Smart Citations
“…The curves go through a critical region at rates below 10 À10 s À1 in which instabilities develop. The critical value is within the estimated rate of emplacement (10 À9 e10 À10 s À1 ) of a pluton (Vigneresse, 2004;Mamtani, 2012). On the presented diagram (Fig.…”
Section: Instability Developments Caused By the Rheologysupporting
confidence: 75%
“…The inset of instabilities (in light grey) occurs at lower strain rates (below 10 À10 s À1 ) when the viscosity curve intersects the critical zone. The critical value of 10 À10 s À1 fits with the high rate estimated for magma emplacement (Mamtani, 2012). on melting, and could be considered as restitic on low degree of reheating.…”
Section: System Stabilitysupporting
confidence: 67%
See 1 more Smart Citation
“…However, whereas fractal patterns of various geological deformation structures have been studied at various scales 10,11 , fractal spatial distributions of mineral deposits have been studied mainly at regional-scales 14 . Some studies have reported that micro-scale fractal geometries of metal-bearing quartz veins in secondary structures are similar to regional-scale fractal geometries of major structures 12,13 , whereas some studies have linked micro-scale fractal distributions of ore/gangue minerals to regional-scale structural processes 14,15 . No studies, however, have linked micro-scale patterns of ore/gangue minerals to local-scale structures at/near mineral deposits to support the proposition that mineral deposits are fractals.…”
Section: Introductionmentioning
confidence: 99%
“…prove dislocation glide in naturally deformed polymineralic rocks (e.g., Mamtani et al, 2011;Kontny et al, 2012). In addition, since a deformation mechanism map is theoretically calculated based on experiments done on single crystals of a mineral, it may not necessarily be valid for that mineral in a polymineralic rock (e.g., Mamtani, 2012). Thus, the present investigation involving microscale (SEM-EBSD) and nanoscale (TEM) studies enables us to evaluate the deformation mechanism of magnetite in polymineralic rocks.…”
Section: Discussionmentioning
confidence: 99%